Highlights of ADB cooperation with civil society organizations 2016. (Metro Manila, Philippines Asian Development Bank, 2017)
ADB recognizes that cooperation with civil society organizations (CSOs) helps improve the quality of its development services. The Midterm Review of ADB Strategy 2020 recommends that CSOs should be more involved in the design and implementation of projects, as well as in the monitoring of project activities and outputs. As ADB celebrates its 50th year, it continues to address the changing needs of its developing member countries.
Keywords: Public administration -- Developing countries; Electronic books